Increased functional connectivity in a population at risk of developing Parkinson's disease. (November 2021) - Binder, Tobias; Hobert, Markus A.; Pfrommer, Teresa; Leks, Edyta; Granert, Oliver; Weigl, Benedikt; Ethofer, Thomas; Erb, Michael; Wilke, Marco; Maetzler, Walter; Berg, Daniela
Abstract: Background: While the concept of prodromal Parkinson's disease (PD) is well established, reliable markers for the diagnosis of this disease stage are still lacking. We investigated the functional connectivity of the putamina in a resting-state functional MRI analysis in persons with at least two prodromal factors for PD, which is considered a high risk for PD (HRPD) group, in comparison to PD patients and controls. Methods: We included 16 PD patients, 20 healthy controls and 20 HRPD subjects. Resting state echo planar images and anatomical T1-weighted images were acquired with a Siemens Prisma 3 T scanner. The computation of correlation maps of the left and the right putamen to the rest of the brain was done in a voxel-wise approach using the REST toolbox. Finally, group differences in the correlation maps were compared on voxel-level and summarized in cluster z-statistics. Results: Compared to both PD patients and healthy controls, the HRPD group showed higher functional connectivity of both putamina to brain regions involved in execution of motion and coordination (cerebellum, vermis, pre- and postcentral gyrus, supplementary motor area) as well as the planning of movement (precuneus, cuneus, superior medial frontal lobe). Conclusions: Higher functional connectivity of the putamina of HRPD subjects to other brain regions involved in motor execution and planning may indicate a compensatory mechanism. Follow-up evaluation and independent longitudinal studies should test whether our results reflect a dynamic process associated with a prodromal PD state. Highlights: Individuals with multiple risk factors for PD show increased putaminal functional connectivity in resting-state fMRI. Putaminal connectivity is increased to brain regions involved in motor execution and planning. Increased putaminal connectivity may depict a compensatory mechanism. Compensatory mechanisms that enable smooth motion planning despite ongoing pathology contribute to late clinical onset and detection of PD.